Song, Y., Geng, K., Zhang, B., Hyde, K.D., Zhao, W.-S., Wei, J.-G., Kang, J.-C. & Wang, Y. (2013) Two new species of Pestalotiopsis from Southern China. Phytotaxa 126 (1), 22–30. - Song, Yu; Geng, Kun; Zhang, Bin; Hyde, Kevin D.; Zhao, Wen-Sheng; Wei, Ji-Guang; Kang, Ji-Chuan; Wang, Yong (Phytotaxa, 2013)
The authors of paper “Two new species of Pestalotiopsis from Southern China” regret that the affiliation of Bin Zhang is incorrect. His affiliation is “Plant Protection and Quarantine Station, Guiyang City, 550081, People’s Republic of China”, thus the superscript of his name should be changed from “1” to “3”.